Influence of Strategic Leadership, Entrepreneurial Orientation, and Flexibility Strategy on the Performance of Digital Start-Up in Indonesia - Syamsulbahri; Barjoyai Bardai; Abdoulrahman Aljounaidi; Alharath Ateik; Mukhtar Idris Abu Baker (Journal Management & Economics Review (JUMPER), 2026)
This study examines the influence of strategic leadership, entrepreneurial orientation, and flexibility strategy on the performance of digital start-ups in Indonesia. Grounded in dynamic capabilities theory, the research investigates both the direct and indirect relationships among these constructs, including the mediating role of entrepreneurial orientation and the moderating role of flexibility strategy. A quantitative approach was employed using a cross-sectional survey of 187 founders, CEOs, and senior managers of digital start-ups across various sectors in Indonesia. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that strategic leadership, entrepreneurial orientation, and flexibility strategy each have a positive and significant effect on digital start-up performance. Entrepreneurial orientation emerges as the strongest direct predictor of performance and partially mediates the relationship between strategic leadership and performance. Additionally, flexibility strategy significantly strengthens the relationship between entrepreneurial orientation and performance, indicating that adaptive capability enhances the effectiveness of entrepreneurial initiatives. The model explains a substantial proportion of variance in start-up performance, demonstrating strong predictive power. The findings highlight the importance of integrating visionary leadership, entrepreneurial strategic posture, and organizational flexibility to achieve sustainable competitive advantage in Indonesia’s dynamic digital economy. This study contributes to entrepreneurship and strategic management literature by offering an integrated framework for understanding digital start-up performance in emerging markets and provides practical implications for founders, managers, and policymakers seeking to strengthen the digital entrepreneurial ecosystem.